The bone clocks [compact disc, unabridged] : a novel - Mitchell, David (David Stephen) (Recorded Books, 2014)
Following a scalding row with her mother, fifteen-year-old Holly Sykes slams the door on her old life. But Holly is no typical teenage runaway: A sensitive child once contacted by voices she knew only as 'the radio people,' Holly is a lightning rod for psychic phenomena. Now, as she wanders deeper into the English countryside, visions and coincidences reorder her reality until they assume the aura of a nightmare brought to life.